Catalyzing Regional Influence: The United Arab Emirates’ and Qatar’s Bids for Educational Leadership in the MENA Region through International Education Hubs - Adam, Edmund; Adam, Neil (International Higher Education, 2024)
<h3 id="qatar-and-the-united-arab-emirates-are-amplifying-their-focus-on-international-education-hubs-to-boost-their-regional-leadership-and-project-soft-power-in-the-mena-region-sensing-a-propitious-geopolitical-climate-the-two-countries-aim-to-enhance-their-regional-influence-through-education-however-the-capacity-of-education-hubs-to-support-the-quest-for-regional-leadership-can-be-diminished-by-entrenchment-in-conventional-organizational-design-and-exposure-to-sustainability-risks" data-pm-slice="1 1 []">Qatar and the United Arab Emirates are amplifying their focus on international education hubs to boost their regional leadership and project soft power in the MENA region. Sensing a propitious geopolitical climate, the two countries aim to enhance their regional influence through education. However, the capacity of education hubs to support the quest for regional leadership can be diminished by entrenchment in conventional organizational design and exposure to sustainability risks.